Metachronous Liver Metastasis Resulting from Early Gastric Carcinoma after Subtotal Gastrectomy Following Endoscopic Resection: A Case Report - Oh, Sung Jin (J Gastric Cancer, 2015)
Hepatic metastasis of early gastric cancer (EGC) following subtotal gastrectomy with lymphadenectomy is rare. We report the case of a 61-year-old male patient who was diagnosed with EGC that was initially treated using endoscopic submucosal dissection (ESD) and subsequently underwent laparoscopic subtotal gastrectomy. Histopathological examination of the patient's ESD specimen showed a moderately differentiated tubular adenocarcinoma invading the submucosa without lymphatic invasion. The deep margin of the specimen was positive for adenocarcinoma, and he subsequently underwent laparoscopic distal gastrectomy. The patient developed liver metastasis 15 months after the operation and then underwent liver resection. Histology of the resected specimen confirmed the diagnosis of two foci of metastatic adenocarcinoma originating from stomach cancer. Immunohistochemical analysis of the specimen demonstrated overexpression of human epidermal growth factor receptor 2. The patient was treated with trastuzumab in combination with chemotherapy consisting of capecitabine and cisplatin. Twenty-four months after the operation, the patient remained free of recurrence.